Pengembangan Media Pembelajaran Maket Ka’bah pada Materi Haji di Kelas IX MTs Hidayatullah Kota Palopo - Sari, Sindi Antika; Faruq, Umarul (Indonesian Journal of Islamic Educational Review, 2024)
This study aims to develop and evaluate the effectiveness of the Ka'bah model as a learning media in teaching the Hajj pilgrimage material to ninth-grade students at MTs Hidayatulah, Paropo City. The Ka'bah model is utilized as a tool to enhance understanding of Islamic values and the importance of the Hajj pilgrimage in Islam. By applying the ADDIE model in media development, this research integrates Vygotsky's constructivist theory to enhance students' learning experiences through social interaction and active learning. The research findings indicate that the Ka'bah model received high ratings from media experts and material specialists, as well as positive feedback from students through questionnaires. The Ka'bah model is not only effective as a reference material but also practical in learning. This demonstrates that the use of the Ka'bah model effectively promotes interactive and engaging understanding of the Hajj material among students. This study contributes to the literature by emphasizing the importance of creative and interactive learning media in education, and it paves the way for further development in the design and implementation of innovative learning media. However, the study acknowledges limitations in generalizing findings to other contexts and learning materials, thus further research is needed to provide a more comprehensive understanding.